The Correlation Between Teacher’s Teaching Style and Students’ English Learning Achievement - Samsul, Cheria Tri De Afril; Muhayyang, Maemuna; Korompot, Chairil Anwar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This research aims to determine teacher's teaching style, students' English learning achievement, and the correlation between teacher's teaching style and students' English learning achievement. This research used a quantitative approach and the correlation method. The sample in this research was 20 students of class XI IPA 1 SMAN 2 Kendari, and the sample was selected using a purposive sampling technique. Data was obtained from questionnaire and test answers from 20 respondents and 1 English teacher which were then correlated. The results of the research concluded that: (1) the dominant teacher teaching style chosen by respondent was interactional teaching style, second was personal teaching style, third was technology, and finally classical. So, it can be concluded that teacher more often use an interactional teaching style, meaning that teachers and students are interdependent, both are subjects of learning, and neither is considered good or vice versa, (2) The English learning achievement of class XI IPA 1 SMAN 2 Kendari is in the medium category. This can be seen in the students' English test results with an average score of 53.25. So, achievement in this research is the result achieved by students in the learning process by trying to master the knowledge, skills or attitudes as expected. Low learning achievement can be influenced by internal factors and external factors that were not studied by researchers, and (3) the correlation between teacher teaching style and students' English learning achievement obtained a rxy result of 0.512 (between 0.410 - 0.600) where the two variables have a moderate degree of correlation and positive correlation form. It can be concluded that the hypothesis which states that there is a relationship between the teacher's teaching style and students' English learning achievement is accepted. So, whatever teaching style a teacher uses should be in accordance with the learning objectives so that it can support the student learning process and obtain optimal results.Keywords-- Teacher’s Teaching Style, Learning Achievement